China’s Race to Rise and Shine in High Technology - SARMIZA PENCEA (Global Economic Observer)
This article looks at the nowadays heated competition for technological supremacy between China, a rising technological power, and the US, the current global authority in high technology and grand creator of new industries, innovative products, processes and services. It mainly addresses China’s race to not only catch up, but replace the current global leaders in research, development and innovation, in a huge national push to break the technological dependency on the US and on the other technologically advanced nations and, making use of all the available means, legitimate or not, to accelerate the nation’s progress towards self-reliance, self-sufficiency, the innovation-driven economy and to the final goal of reaching global technological dominance.